Bonus Question: How Does Flexible Incentive Pay Affect Wage Rigidity? - Meghana Gaur; John Grigsby; Jonathon Hazell; Abdoulaye Ndiaye (CESifo GmbH, 2024)
We introduce dynamic incentive contracts into a model of inflation and unemployment dynamics. Our main result is that wage cyclicality from incentives neither affects the slope of the Phillips curve for prices nor dampens unemployment's response to shocks. The impulse response of unemployment in economies with flexible, procyclical incentive pay is first-order equivalent to that of economies with rigid wages. Likewise, the slope of the Phillips curve is the same in both economies. This equivalence is due to effort fluctuations, which make marginal costs rigid even if wages are flexible. Our calibrated model suggests that 46% of the wage cyclicality in the data arises from incentives, with the remainder attributable to bargaining and outside options. A standard model without incentives calibrated to weakly procyclical wages matches the impulse response of unemployment in our incentive pay model calibrated to strongly procyclical wages.
Keywords: 330; Leistungsentgelt; Leistungsanreiz; Arbeitslosigkeit; Inflation; Phillips-Kurve; Lohnrigidität; Arbeitsproduktivität; Theorie